2021
DOI: 10.15408/ijee.v1i1.17701
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Voices on Lecturers’ Written Corrective Feedback (WCF) in Their Writing Tasks

Abstract: Although studies on Written Corrective Feedback (WCF, hereafter) have been increasingly prevalent in the last few years, inquiries on how advisory students perceive the lecturers’ feedback on their writing tasks have been likely scarce, especially in Indonesian Higher Education Institutions (HEIs) contexts. This study examines the students’ perception and evaluation of the lecturers’ WCF in response to errors and inaccuracies in their academic writing tasks. Through an online survey questionnaire distributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…This is presumably what Irwin (2017) claimed most WCF provided by the instructors are likely to be teacher-centred and students often play a passive role in learning. This trend has also been supported by a study, claiming that direct forms of WCF were popular and most preferred by tertiary students (Adrefiza, Hidayat, & Fortunasari 2021;Adrefiza & Fortunasari, 2020). Data distributions in items (3) and (4) further support the phenomenon where students' greater responses displayed their preferences towards WCF with real correction and not the one with cues and prompts.…”
Section: Opinionmentioning
confidence: 53%
See 2 more Smart Citations
“…This is presumably what Irwin (2017) claimed most WCF provided by the instructors are likely to be teacher-centred and students often play a passive role in learning. This trend has also been supported by a study, claiming that direct forms of WCF were popular and most preferred by tertiary students (Adrefiza, Hidayat, & Fortunasari 2021;Adrefiza & Fortunasari, 2020). Data distributions in items (3) and (4) further support the phenomenon where students' greater responses displayed their preferences towards WCF with real correction and not the one with cues and prompts.…”
Section: Opinionmentioning
confidence: 53%
“…WCF is beneficial in accelerating students' independent learning and encourages personal interaction between students and the instructors, especially when it is appropriately delivered and addressed following the students' expectation and preferences (Stracke & Kumar, 2010;Adrefiza & Fortunasari, 2020). The inappropriate practice of WCF, however, is said to potentially account for discouragement in the students learning (Adrefiza, Fortunasari, & Hidayat, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional comment from the feedback can help students get detailed information about their assignments (Gielen et al, 2010). Feedback is important; students can review and focus on their previous subject (Adrefiza et al, 2021;Wahyuni, 2017). Gielen et al (2010) showed why feedback could improve students' learning.…”
Section: Discussionmentioning
confidence: 99%
“…It is a must for students to study at home using a learning platform as an alternative for offline learning. At the same time, teachers also prepare online learning materials to be accessible by students so that the learning can take place digitally (Syamsuriza et al, 2021). One example of the online learning process is by use of video conferencing and a learning management system (Widyanto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%